Implementasi LINQ Pada Aplikasi Student Helper - Sugianto Palar (STMIK Budi Darma, 2018)
Based on the research conducted by the author, currently programmers are still doing a long routine in processing data and besides that the demand for mastering many technologies is getting bigger along with the wider scope of application. LINQ is here to simplify all coding routines and minimize unnecessary repetition. The purpose of this study is (1) To simplify the routine of accessing data, (2). Test the Student Helper application which is an example of LINQ implementation. This Student Helper was built using Visual Basic programming language 9. So that the author's goals can be achieved, the writer collects data with literature studies and through internet forum media. For system testing, the black-box method is used. From the results of testing showing the Student Helper designed using LINQ can run well and easily.